Gas chromatographic–mass spectrometric analysis of sunscreens and their effects on mice liver and kidney enzyme function - AL-Eitan L; Aljamal HA; Alkhatib RQ (Dove Medical Press, 2018)
Laith N AL-Eitan,1,2 Hanan A Aljamal,1 Rami Q Alkhatib1,2 1Department of Applied Biological Sciences, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of Biotechnology and Genetic Engineering, Jordan University of Science and Technology, Irbid 22110, Jordan Background: Sunscreens are one of the most widely used products among cosmetics and personal care products. Recent studies have shown that some of sunscreen formulations may contain toxic, carcinogenic, or even nonallowed chemicals that may affect skin, cells, and hormones. Materials and methods: This study aimed to develop and validate a method that allows the determination of sunscreen ingredients by gas chromatography–mass spectrometry (GC–MS). Analysis of original sunscreen products (n=5) from a licensed pharmacy and counterfeit sunscreen products (n=5) from local markets in Jordan was performed using GC–MS. pH stability of the sunscreen samples were also monitored under different storage temperatures. Topical application of sunscreens on mice skin was conducted to study their effects on liver and kidney enzymes’ function. Results: In terms of pH stability, there is a significant change in pH at different degrees of temperature between the products. Diethyl phthalate (DEP) was detected in two counterfeit products and was not mentioned on the ingredients’ label. DEP was reported for its percutaneous absorption and systemic uptake in the literature. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were significantly increased with a P<0.005 in some groups treated with original sunscreens under sun radiation. Creatinine showed a significant decrease in some groups treated with original and counterfeit sunscreens, while blood urea nitrogen (BUN) showed no differences. Conclusion: This study presents a method that allows the scanning and profiling of sunscreen ingredients as well as investigates their stability, permeation, and toxicity. Profiling of sunscreen product, changing in pH stability, and analyzing kidney and liver enzymes’ level would be of a great impact on products’ safety and consumers’ health. Keywords: skin absorption, sunscreening agents, aspartate aminotransferases, alanine transaminase, cosmetics, urea